Green, How I Want You Green - Stramljič Breznik, Irena; Plemenitaš, Katja (Slavia Centralis, 2023)
The article presents a corpus study of the use of the term green in the context of environmental changes compared to its general use. The main part of the article presents a corpus analysis of the word green using the Gigafida 2.0 corpus and the Termania terminological source. The research shows that in the Gigafida 2.0 corpus, the strongest collocations containing the adjective green with the meaning of environmental protection refer to political parties and activities (green coalition, green alternative) and terms related to economy and tourism (green energy, green destination, green economy). Interestingly, the popular term green transition is not among the strongest collocations. We assume this is due to this expression becoming more established in the period no longer covered by the Gigafida 2.0 corpus.
Keywords: the adjective green, environment, corpus, collocations, terminology